2021
DOI: 10.1097/j.pain.0000000000002320
|View full text |Cite
|
Sign up to set email alerts
|

Antagonism of the mu-delta opioid receptor heterodimer enhances opioid antinociception by activating Src and calcium/calmodulin-dependent protein kinase II signaling

Abstract: The opioid receptors are important regulators of pain, reward, and addiction. Limited evidence suggests the mu and delta opioid receptors form a heterodimer (MDOR), which may act as a negative feedback brake on opioid-induced analgesia. However, evidence for the MDOR in vivo is indirect and limited, and there are few selective tools available. We recently published the first MDOR-selective antagonist, D24M, allowing us to test the role of the MDOR in mice. We thus cotreated CD-1 mice with D24M and opioids in t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 53 publications
1
9
0
Order By: Relevance
“…We showed that this compound was ~90‐fold selective for the MDORH over either monomer and reduced morphine withdrawal in mice (Olson et al, 2018). We further showed that D24M suppressed opioid anti‐nociception via suppression of Src and CaMKII signalling in the brain, also supporting this hypothesis (Keresztes et al, 2022). These results are more clear for the role of the MDORH, because they use a ligand with a high selectivity and defined molecular pharmacology.…”
Section: Opioid Receptor Heterodimerssupporting
confidence: 86%
“…We showed that this compound was ~90‐fold selective for the MDORH over either monomer and reduced morphine withdrawal in mice (Olson et al, 2018). We further showed that D24M suppressed opioid anti‐nociception via suppression of Src and CaMKII signalling in the brain, also supporting this hypothesis (Keresztes et al, 2022). These results are more clear for the role of the MDORH, because they use a ligand with a high selectivity and defined molecular pharmacology.…”
Section: Opioid Receptor Heterodimerssupporting
confidence: 86%
“…In addition to this previously unidentified negative feedback mechanism through AMPK, other negative feedback signaling molecules and circuits have been identified that restrain opioid activity in both the brain and spinal cord. Work from our laboratory and others has shown that the μ and δ opioid receptors heterodimerize and that this heterodimer reduces the antinociceptive effects of opioids (25,26). Cholecystokinin neurons in the rostroventral medulla act as an "anti-opioid" system to reduce opioid-induced analgesia and enhance side effects (27,28).…”
Section: Discussionmentioning
confidence: 99%
“…The KOR selective antagonist norBNI (10 mg/kg, s.c.) , and NXAZ (10 mg/kg, i.p. ) , were administered 120 min before the hot plate trial. The delta latency (s) for each animal was calculated using this equation: Δlatency (s) = latency after treatment (s) – baseline latency (s).…”
Section: Methodsmentioning
confidence: 99%